Implementasi Kebijakan Pemerintah tentang Migrasi Nomenklatur Perubahan Nama Program Studi di Universitas Tulungagung - Surjanti Surjanti; Retno Sari Dewi; Anang Sugeng Cahyono; Erly Pangestuti (Jurnal Supremasi, 2022)
The issuance of Permendikbudristek concerning the naming of Study Programs (Prodi) which was followed up by the nomenclature of changing the name of Study Programs and /or form of Higher Education (PT) resulted in a major impact on PT. Based on a copy of the Decree of the Minister of Research, Technology and Higher Education Number 234/KPT/1/2019, Tulungagung University migrated 2 (two) study programs, namely the Legal Studies Study Program to the Law Study Program and the State Administration Science Study Program to the Public Administration Study Program. This study analyzes the implementation of the migration process policy of changing the name of the Study Program at Tulungagung University as well as identifying the impacts and constraints during the PD DIKTI data migration process. Through empirical legal research using a sociological juridical approach, research shows that the implementation of the migration process has been carried out following the mechanisms, stages, and coordination with the LLDIKTI Region 7 East Java, can be completed in two years, and the parties affected by the migration process include all academics and institutions. One of the biggest obstacles in the migration process is the incomplete data input on the reporting of the old study program feeder reporting where the migration requires the validity of the previous data.